Prosedur Pemeriksaan Msct Abdomen Kontras Dengan Klinis Tumor Lower Abdomen Di Instalasi Radiologi RS Kupang - Natalia Imelda Seran; I Putu Eka Juliantara; Cokorda Istri Ary Widiastuti (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Background: CT (Computed Tomography) Scan modality is very useful for obtaining a diagnosis of tumors in the abdominal cavity. The procedure carried out in abdominal MSCT uses contrast media. The contrast media commonly used in abdominal MSCT examinations can be intravenous, oral and anal. Kupang Hospital uses contrast media intravenously, orally and anally. The aim of this study was to determine the procedure for examining abdominal MSCT with clinical lower abdominal tumors using a multiphase technique using intravenous contrast media in the form of iodine water soluble with a dual syringe injector and NaCl liquid and orally with a volume of 750 ml of mineral water mixed with 5 ml of contrast media to drink before The examination then takes place via anal examination in the form of negative water contrast media mixed with iodine water soluble contrast media with a 50 cc syringe and also to find out the reasons for using contrast media intravenously, orally and anally in abdominal MSCT examinations with clinical lower abdominal tumors. Method: This research design is qualitative with a case study approach. The subjects of this study were patients with clinical lower abdominal tumors. Research respondents were 2 Radiographers, 1 Radiology Specialist. The data collection method was taken by observation, Focus Group Discussion (FGD) and documentation, then data analysis and conclusion drawing were carried out. Results: The results of this study are about the abdominal MSCT examination procedure and the reasons for using contrast media injection techniques with clinical lower abdominal tumors in the Kupang Hospital Radiology Installation. Conclusion: The use of the technique of intravenous administration of contrast media aims to anatomically visualize vascularization, distinguish blood vessels from masses, determine the level of vascular displacement or invasion by tumors and by inserting contrast media orally it aims to provide opacification of the intestine and assist in diagnosing existing abnormalities in the intestine such as ulceration, perforation, obstruction, and space occupying lesions then through anal purposes to fill the large intestine, able to provide an overview of colonic distension and colon cancer. The use of contrast media injection techniques via intravenous, oral and anal is because the patient can make preparations as expected .